“A WAY TO DO AN INTEGRAL HISTORY OF SOCIETY”. SOCIAL CLASSES AND SOCIABILITY ON VÍCTOR HUGO ACUÑA ORTEGA’S HISTORIOGRAPHY. - García, George I. (2013)
This essay analyzes Víctor Hugo Acuña’s studies from two points of view: from his methodological and theoretical influences and from his substantial thesis. It finally draws conclusions based on some critical remarks.